2022
DOI: 10.3389/fvets.2022.801636
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Approach for Compulsive Behavior in Dogs: A Case Report

Abstract: Compulsive disorder is a debilitating condition affecting both humans and animals, characterized by intrusive thoughts and recurring out-of-place behaviors. Among them, tail chasing might represent one of the most common traits in compulsive dogs. Herein, we reported the case of a 7-year-old intact male German Shepherd mixed-breed dog, presenting with tail chasing behavior. He underwent a first behavioral evaluation 1 year before (at the age of 6), when he injured himself with severe wounds at level of the tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…Lockdown puppies also exhibited increased non-social fearfulness attitudes; this is unsurprising, considering that a recent study reported that lockdowns in Spain led to an increase in the fear of loud or sudden noises [ 32 ]. Dogs with recurrent non-social fears generally experienced a poor socialization process during puppyhood, thus suggesting that puppies should be introduced to stimuli and conditions they are likely to encounter as adults, improving the plasticity of their behavior, in order to create well-balanced adult dogs who are able to cope with new contexts [ 56 , 57 , 58 , 59 , 60 , 61 ]. In the light of the severe developmental alterations in puppies born during COVID-19 pandemic lockdown, which have compromised their physiological behaviors, it is imperative that we find alternative strategies that allow “patients” to cope with such psychosocial disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lockdown puppies also exhibited increased non-social fearfulness attitudes; this is unsurprising, considering that a recent study reported that lockdowns in Spain led to an increase in the fear of loud or sudden noises [ 32 ]. Dogs with recurrent non-social fears generally experienced a poor socialization process during puppyhood, thus suggesting that puppies should be introduced to stimuli and conditions they are likely to encounter as adults, improving the plasticity of their behavior, in order to create well-balanced adult dogs who are able to cope with new contexts [ 56 , 57 , 58 , 59 , 60 , 61 ]. In the light of the severe developmental alterations in puppies born during COVID-19 pandemic lockdown, which have compromised their physiological behaviors, it is imperative that we find alternative strategies that allow “patients” to cope with such psychosocial disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, owners are encouraged to take note of what their own roles are, and to establish a fully empathic relationship with the dog. Environmental modification might be associated with the management of different parameters, and is aimed at reducing the performance or intensity of the pathologic behavior; techniques may involve (a) exposure to positive stimuli, (b) consistent and predictable consequences that use rewards, rather than punishment, to encourage desirable behaviors, offering adequate enrichment to meet the dogs, and (c) paying attention to the identification and removal (or reduction) of stressors that activate problematic traits [ 26 , 60 ]. Finally, based on our research experience at the academic teaching hospital, behavioral shaping might be improved through a tailored therapeutic intervention; such interventions are characterized by the use of olfactory and cooperative learning, as well as calming and relaxing activities, including resting on a mat, or chewing on an appropriate chew toy.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs also play an increasing role as a co-therapist or advocate for people with psychological or physical disabilities, especially those animals residing or visiting prisons and nursing homes, thereby turning into improved mood, decreased physiological distress, depression, dementia and loneliness [9,38,39]. Despite the deep human-dog relationship there are multiple dysfunctional aspects behind this to be considered, like excessive aggression, fear and anxiety, or even abnormal repetitive behavior (d'Angelo et al, 2022-Retrospective analysis of dog bites in Southern Italy-Ciência Rural-Accepted manuscript) [3,40], becoming a victim of Anthropomorphism or animal hoarding [4], or ending up imprisoned in kennels. In this view, the safety of humans in the one health perspective should start from the following parameters:…”
Section: The Impact Of a Shelter On Humansmentioning
confidence: 99%
“…On the other hand, given their ability to feel positive and negative emotions, animals can even benefit from humans, thus highlighting the importance of developing practical welfare assessment indicators either for husbandry or companion animals [2]. Despite the deep relationship between humans and dogs, there are multiple dysfunctional issues to take into account, including excessive aggression, fear and anxiety, or abnormal repetitive behaviors [3], thereby becoming victim of anthropomorphism, animal hoarding [4], and eventually ending up imprisoned in kennels. Unfortunately, the kennel is considered one of the crucial concerns of the human-animal bond, since it is very often regarded as animals dump, a place where dogs exile and thus a burden on society.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, given their ability to feel both positive and negative emotions, animals can even benefit from humans, thus highlighting the importance of developing practical welfare assessment indicators either for husbandry or pets [ 2 ]. Despite the deep connection between humans and dogs, there are multiple dysfunctional issues arising in these animals to take into account, including excessive interspecies aggression [ 3 ], fear and anxiety, or abnormal repetitive behaviors [ 4 ], thereby becoming victims of anthropomorphism, animal hoarding [ 5 ], and eventually ending up in kennels, which very often are regarded as animal dumps, a place where they spend the rest of their life in exile. Given that the killing of kenneled dogs is not allowed in Italy, unless they are suffering from untreatable diseases or proven to be extremely dangerous to human health [ 6 ], such a no-kill policy can cause the shelters to be very generally thronged and represents a burden on society [ 7 ].…”
Section: Introductionmentioning
confidence: 99%